Improved microporous membrane separators for lithium ion rechargeable batteries and related methods

KR103019059B1Active Publication Date: 2026-09-15CELGARD LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020247009053
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2014-11-26
Filing Date
2015-11-24
Publication Date
2026-09-15
Estimated Expiration
2035-11-24

Smart Images

  • Figure 112024030163520-PAT00002_ABST
    Figure 112024030163520-PAT00002_ABST
Patent Text Reader

Abstract

According to an example, a multilayer separator for a lithium battery is provided, comprising a dry process membrane of homopolymer polypropylene or a polypropylene blend having a melt flow index (MFI) of 0.8 g / 10 min or less, a thickness of 14 μm or less, a TD tensile strength of 150 kgf / cm2 or more, and a CSI (complex tear index) of 29 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] Cross-reference of related applications

[0002] This application claims priority and benefit of concurrently pending U.S. provisional patent application No. 62 / 084,628, filed November 26, 2014, the entirety of which is incorporated herein by reference.

[0003] The present application relates to one or more novel or improved porous membranes, base films, or battery separators and / or various methods for manufacturing and / or using such membranes, films, or separators. According to at least selected embodiments, aspects, or purposes, the present application or invention relates to one or more novel or improved microporous membrane battery separators, membrane base films, or membrane separators for lithium batteries such as secondary or rechargeable lithium batteries, lithium-ion rechargeable batteries, etc., and / or various methods for manufacturing or using such separators and / or batteries. The specific battery separators of the present invention described herein may have a thickness of less than about 14 μm and may exhibit increased strength performance, defined by a reduced tendency to tear or splittiness compared to known battery separators. Tearing failure modes have been studied, and tearing tendencies or improvements in tearing can be quantified by the novel test method disclosed herein as the Composite Splittiness Index (CSI). The novel or improved membranes, films, or separators described herein may also exhibit improved Gurley as well as other improvements. Background Technology

[0004] Certain prior methods for reducing tearing of microporous battery separator membranes, as well as special tear-resistant or tear-resistant microporous membranes, are known and discussed in U.S. Patent No. 6,602,593. This patent describes a method comprising, among other things, the step of extruding a film precursor by a blown film method and using a blow-up ratio (BUR) of about 1.5 or more during the blown film extrusion.

[0005] U.S. Patent No. 8,795,565 describes, among other things, a biaxial stretching technique involving stretching of both MD and TD of a drying process precursor membrane having a controlled MD relaxation process step. Biaxially stretched membranes, such as the membranes illustrated in FIGS. 1 through 3a and 3b of Patent 8,795,565, may have slightly reduced tearing or ripping. When a biaxially stretched microporous membrane is sensitively tested using a puncture strength test method, the test sample puncture site may be a round hole facing an elongated slit.

[0006] U.S. Patent No. 8,486,556 discloses a multilayer battery separator membrane having increased strength as defined by a mixed permeability strength test, which is a means of force required to cause a short circuit through the separator membrane, among other things. A high molecular weight polypropylene resin having a specific melt flow index was used to manufacture the multilayer separators described in Patent 8,486,556, having a thickness in the range of up to about 25 µm, a porosity in the range of up to about 37%, an ASTM Gurley of 13 to 25 seconds, and an ionic resistance in the range of up to about 2.5 ohms-cm².

[0007] Wet process microporous battery separator membranes are also known, which are typically biaxially stretched and may have fairly balanced MD and TD strength characteristics. Examples of microporous membranes manufactured using a wet process may be disclosed in U.S. Patents No. 5,051,183; No. 6,096,213; No. 6,153,133; and No. 6,666,969.

[0008] Wet process battery separator membranes can be fabricated using high molecular weight polymer resins having molecular weights exceeding 500,000, possibly exceeding 1,000,000, and plasticizers may be used to enable melt extrusion. For example, these plasticizers, which are one or more oils, can be used to melt extrude the high molecular weight resins. The plasticizers may be extracted using one or more solvents as part of the fabrication process. Oil / plasticizer-contaminated solvents from the extraction step of the fabrication process need to be recycled to ensure the extracted solvents and oils are of usable purity quality. This represents an additional energy cost that can be expensive. Therefore, various wet processes for manufacturing battery separators may have disadvantages and various disposal issues, as they are environmentally problematic processes that may require costly solvent treatment, compared to solvent-free, "green," or low-impact dry process methods for manufacturing battery separators (sometimes referred to as the Celgard dry process).

[0009] Various known methods, such as the BUR blown film method, methods involving TD stretching of dry process membranes, and wet process biaxial stretching methods for porous membranes, may not fully optimize the balance of strength or performance characteristics for microporous separators or membrane separators, thin microporous separators or membrane separators, etc.

[0010] Additionally, prior methods or products may not be able to combine strength or performance characteristics by using a solvent-free, environmentally low-impact process to manufacture microporous battery separators or membrane separators having excellent cycle performance and safety in lithium batteries, particularly in high-energy lithium-ion batteries.

[0011] Accordingly, there is a need for novel or improved porous membranes, base films, or battery separators and / or methods for manufacturing and / or using such membranes, films, or separators, dry process microporous battery separators, or membrane separators, having a thickness of about 14 μm or less, a relatively low Gurley number, a relatively high porosity, and strength performance characteristics that are close to or exceed those of wet process battery separators or membrane separators, without the possible undesirable problems associated with various wet process fabrication methods for at least certain battery technologies or fields, energy fields, and / or etc. The problem to be solved

[0012] According to at least selected embodiments, aspects or purposes, the present invention may address one or more of the above requirements and / or the present invention relates to one or more novel or improved porous membranes, base films or battery separators and / or various methods for manufacturing and / or using such membranes, films or separators. According to at least selected embodiments, aspects or purposes, the present application or invention relates to one or more novel or improved microporous membrane battery separators, membrane base films or membrane separators for lithium batteries such as secondary or rechargeable lithium batteries, lithium-ion rechargeable batteries, etc., and / or various methods for manufacturing or using such separators and / or batteries. means of solving the problem

[0013] According to an example, a multilayer separator for a lithium battery is provided, comprising a dry process membrane of homopolymer polypropylene or a polypropylene blend having a melt flow index (MFI) of 0.8 g / 10 min or less, a thickness of 14 μm or less, a TD tensile strength of 150 kgf / cm2 or more, and a CSI (complex tear index) of 29 or more.

[0014] According to an embodiment, a multilayer separator for a lithium battery is provided, comprising a dry process triple film of homopolymer polypropylene or a polypropylene blend having a melt flow index (MFI) of 0.8 or less, a thickness of 14 μm or less, a TD tensile strength of 130 kgf / cm2 or more, and a CSI (complex tear index) of 70 or more.

[0015] The above separator can have a first load peak of puncture strength (PS) of 130 gf or more.

[0016] The above separator can have a porosity of 25% or more.

[0017] The above separator may have an electrical resistance (ER) of 1.5 ohms-cm2 or less and a porosity of 25% or more.

[0018] The above separator can have an MD tensile strength of 1800 kgf / cm2 or more.

[0019] The CSI (complex tear index) of the above separator may be 100 or higher.

[0020] The CSI (complex tear index) of the above separator may be 50 or higher.

[0021] The above separator can have a porosity of 27% or more.

[0022] The above separator can have a porosity of 31% or more.

[0023] The above separator may have a porosity in the range of 30% to 50%.

[0024] The above separator may have a porosity in the range of 31% to 40%.

[0025] The above separator may have a thickness of less than 8 μm.

[0026] According to an embodiment, a single-layer separator for a lithium battery is provided, comprising a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the maximum melt flow index (MFI) is 0.8 g / 10 min, the thickness is 7 μm or less, the first load peak is 131 gf or more, the second load peak is 120 gf or more, the TD tensile strength is in the range of at least 153-207 gf, the MD tensile strength is 1813 gf or more, and the TD elongation measured during the puncture strength test is 464% or more, and the strength performance prediction of the lithium secondary battery microporous membrane is performed through the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during the puncture strength test.

[0027] According to an example, a separator for a lithium battery comprises a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the single dry process layer has a maximum melt flow index (MFI) of 0.8 grams / 10 min and a thickness of 7 μm or less, and the separator has a first load peak of 131 gf or more, a second load peak of 120 gf or more, and a TD tensile strength in the range of 153-207 kgf / cm2 with a maximum TD tensile strength of 207 kgf / cm2, and has a Composite Splittiness Index (CSI) that predicts the strength performance of a lithium secondary battery microporous membrane from the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 131 gf or more, the second load peak is 120 gf or more, and the TD tensile strength is The separator for a lithium battery is 153-207gf or higher, the MD tensile strength is 1813gf or higher, and the TD elongation is 464% or higher, and the separator is a single layer film or a base film.

[0028] According to an example, a separator for a lithium battery comprises a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the single dry process layer has a maximum melt flow index (MFI) of 0.8 grams / 10 min and a thickness of 7 μm or less, and the separator has a maximum TD tensile strength of 207 kgf / cm2 with a TD tensile strength in the range of 153-207 kgf / cm2, and has a Composite Splittiness Index (CSI) that predicts the strength performance of a lithium secondary battery microporous membrane from a first load peak, a second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 131 gf or more, the second load peak is 120 gf or more, the TD tensile strength is 153-207 gf or more, the MD tensile strength is 1813 gf or more, and TD The elongation is 464% or more, and the separator provides a lithium battery separator that is a multilayer separator, a membrane, or a base film.

[0029] According to an embodiment, a separator for a lithium battery is provided, wherein the separator has a dry process triple film of a polypropylene blend having a melt flow index (MFI) of 0.8 g / 10 min or less and a thickness of 14 μm or less as a triple film or base film, and has a Composite Splittiness Index (CSI) of 70 or more for predicting the strength performance of the lithium secondary battery microporous film from a first load peak, a second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 279 gf or more, the second load peak is 277 gf or more, the TD tensile strength is 136-150 gf or more, the MD tensile strength is 2245 gf or more, and the TD elongation is 700% or more.

[0030] The above CSI is based on the test method of the present invention known as the Composite Splittiness Index (CSI), and the CSI value is defined by the following Equation 1, and the CSI may be a function of the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during the puncture strength test.

[0031] [Mathematical Formula 1]

[0032] CSI = (A-|B - A|1.8) x C x (D x E) / 106

[0033] (Here:

[0034] A = First load peak of computer program / thickness, thickness = thickness x (100% - porosity), gf

[0035] B = 2nd load peak / thickness, gf

[0036] C = TD elongation, %

[0037] D = MD tensile strength, gf

[0038] E = TD tensile strength, gf

[0039] The unit of the thickness values ​​is μm.

[0040] According to an embodiment, a separator for a lithium battery comprises one or more polyolefin microporous membranes manufactured according to a dry process, wherein a polyolefin resin is extruded to form the membrane, the pore formation occurs by stretching or further stretching a non-porous, semi-crystalline, extruded polymer precursor in a machine direction, the resin has a melt flow index (MFI) of 0.8 g / 10 min or less, the membrane has a thickness of 7 μm or a maximum thickness of 7 μm; and the membrane has a TD tensile strength of 153-207 kgf / cm2, with a maximum TD tensile strength of 207 kgf / cm2, thereby providing a separator for a lithium battery.

[0041] The above resin may have a melt flow index (MFI) of 0.5 grams / 10 minutes or less.

[0042] According to an example, a separator for a lithium battery is provided having a first load peak of 279 to 392 gf, a CSI (complex tear index) of 88 to 141, a porosity of 40% to 44%, and an ER (electrical resistance) of 1.2 to 1.5 ohms-cm², wherein the separator is a three-layer separator, the total thickness of the separator is 12 to 13.5 μm, the separator comprises one or more microporous polyolefin membranes manufactured according to a dry process, wherein in the dry process a polyolefin resin is extruded to form the microporous polyolefin membrane, the polyolefin resin has a melt flow index (MFI) of 0.8 g / 10 min or less, and the CSI (complex tear index) is defined by the following Equation 1.

[0043] [Mathematical Formula 1]

[0044] CSI = (A-|B - A| 1.8 ) x C x (D x E) / 10 6

[0045] Here:

[0046] A = 1st load peak / thickness x (1 - % porosity)

[0047] B = Second load peak / Thickness

[0048] C = TD elongation

[0049] D = MD tensile strength

[0050] E = TD tensile strength

[0051] (Here, the first and second load peaks are in gram-force units, thickness values ​​are in microns, MD and TD tensile strengths are in gram-force units, and TD elongation is expressed as a percentage.)

[0052] The above separator may have a porosity of 40%, an ER (electrical resistance) of 1.5 ohm-cm², a total thickness of 13.5 μm, a CSI (complex tear index) of 141, a first load peak of 392 gf, and a second load peak of 391 gf.

[0053] The above separator may be used for energy cell applications.

[0054] The above separator may have a TD (transverse) tensile strength of 136 to 150 kgf / ㎠.

[0055] The above separator may have a CSI (complex tear index) of 88, a porosity of 44%, an ER (electrical resistance) of 1.2 ohms-cm², a total thickness of 12 μm, a first load peak of 279 gf, and a second load peak of 277 gf.

[0056] The separator comprises one or more microporous polyolefin membranes manufactured according to the dry process, wherein a polyolefin resin is extruded in the dry process to form the microporous polyolefin membrane, and the polyolefin resin may have a melt flow index (MFI) of 0.5 grams / 10 min or less.

[0057] According to at least selected embodiments, aspects or purposes, the present invention may address one or more of the above requirements and / or the present invention relates to one or more novel or improved porous membranes, base films or battery separators and / or various methods for manufacturing and / or using such membranes, films or separators. According to at least selected embodiments, aspects or purposes, the present application or invention relates to one or more novel or improved microporous membrane battery separators, membrane base films or membrane separators for lithium batteries such as secondary or rechargeable lithium batteries, lithium-ion rechargeable batteries, etc., and / or various methods for manufacturing or using such separators and / or batteries.

[0058] The specific battery separators of the present invention described herein may have a thickness of about 14 μm or less and may exhibit increased strength performance, defined by a reduced tendency to tear or splittness when compared to known battery separators. Tearing failure modes have been studied, and improvements in tearing or splittness may be quantified by the novel test method disclosed herein as a composite tear index (CSI). The novel or improved membranes, films, or separators described herein may also exhibit improved glyphs as well as other improvements.

[0059] According to at least selected embodiments, aspects, or purposes, the present invention addresses one or more of the above requirements and relates to one or more novel or improved porous membranes, base films, or battery separators (or membrane separators) and / or various methods for manufacturing and / or using such membranes, films, or separators. According to at least selected embodiments, aspects, or purposes, the present invention relates to one or more novel or improved microporous membrane battery separators, membrane base films, or membrane separators (or membranes acting as one or more layers in a battery separator) for lithium batteries such as lithium-ion rechargeable batteries, and / or various methods for manufacturing or using such separators or films. The particular battery separators of the present invention described herein may have a thickness of about 14 μm or less and may exhibit increased strength performance, defined by reduced tearing or rips compared to known battery separators. Tearing failure modes have been studied, and tearing or tearing improvement can be quantified by the novel test method disclosed herein as a composite tear index (CSI). The novel or improved membranes, films, or separators described herein may also exhibit improved gauls as well as other improvements and may be adapted particularly for energy fields.

[0060] The present application relates to one or more novel or improved porous membranes, base films or battery separators and / or various methods for manufacturing and / or using such membranes, films or separators. According to at least selected embodiments, aspects or purposes, the present invention relates to one or more novel or improved microporous membrane battery separators for lithium batteries, such as lithium-ion rechargeable batteries, and various methods for manufacturing or using such separators. The preferred battery separators that may be described herein may have a thickness of less than about 14 µm, less than about 13 µm, or less than about 8 µm and may surprisingly exhibit increased strength performance, defined by reduced tearing, compared to known battery separators of the same (or greater) thickness. Tearing or improvement in tearing can be quantified by the test method disclosed herein as a composite tear index (CSI), and the novel or improved separators described herein may have a CSI of 29 to 139 and may also exhibit improved tearing as well as other improvements.

[0061] The present invention relates to a novel or improved microporous battery separator for a lithium-ion rechargeable battery in at least selected embodiments and / or related methods for manufacturing and / or using such separator. A particular dry-process battery separator or membrane separator of the present invention has a thickness of about 14 μm or less and has increased strength performance as defined by tear resistance or reduced tearing, which is quantified by a novel test method known as the Composite Tearing Index (CSI).

[0062] The blow-up ratio method may involve radial expansion of the blown film from an annular die. An increased level of crystalline structure orientation in the transverse direction (TD) can be achieved in extruded films using a blow-up ratio greater than about 1.5. This increased crystalline structure orientation in TD, achieved by the radial expansion of the blown-extruded precursor film, can further improve TD tensile strength and TD elongation and result in less tearing of the stretched microporous film.

[0063] Round perforated holes can exhibit reduced tearing tendency or tearing of the membrane, reinforced tear resistance, balanced TD and MD strength and good TD elongation, and thus excellent strength performance can be predicted when such membrane is used as one or more layers of a battery separator, membrane separator, base film or lithium-ion battery.

[0064] Various known methods, such as BUR blown film methods, methods involving TD stretching of dry process membranes, and wet process biaxial stretching methods for porous membranes, may not be able to fully optimize the balance of the following strength or performance characteristics for microporous separators or membranes having a thickness of about 14 μm or less:

[0065] ㆍ Excellent MD and TD tensile strength;

[0066] ㆍ Excellent TD elongation;

[0067] ㆍ High puncture strength;

[0068] ㆍ Desirable Gally; and / or

[0069] ㆍ Absence of tearing.

[0070] Additionally, to manufacture a microporous battery separator membrane having excellent cycle performance and safety in lithium batteries such as lithium-ion batteries, it may be desirable to combine the characteristics identified above by using a solvent-free, environmentally low-impact process.

[0071] Novel or improved microporous battery separators have been developed for use in lithium-ion rechargeable batteries. The separator of the present invention is preferably a dry-process single-layer or multilayer microporous battery separator membrane fabricated using a high molecular weight, low melt flow index polymer resin or a blend of high molecular weight, low melt flow index polymer resins, which, when extruded, produce a precursor membrane having an internal microstructure with a relatively high level of crystalline lamellar orientation without requiring the use of plasticizers. This high level of crystalline lamellar orientation can provide improved strength performance of the separator of the present invention compared to known separators. The grade of crystallinity of the lamellar structure of the nonporous precursor membrane can also influence the formation of micropores during the stretching step of dry-process fabrication of the microporous separator, base separator, or base film (adapted to be coated on one or both sides or laminated on one or more other layers), or membrane (serving as one or more layers of the separator or base film).

[0072] Manufacturers of batteries for the consumer electronics industry may prefer membrane separators or thin microporous membrane battery separators having a thickness of about 14 μm or less to improve the cycle life of lithium-ion secondary batteries and optimize energy density. The battery separator or membrane of the present invention is a "thin" battery separator or membrane having a thickness of about 14 μm or less, as well as improved strength performance, such as reduced tearing, or reduced tearing as a result of perforation, compared to other separators of the same thickness made by the same process, such as the conventional dry stretch process.

[0073] The separator or membrane of the present invention of at least selected embodiments can achieve improvements over conventional battery separators or membranes, as it provides a thin, dry-process separator or membrane having a thickness of about 14 μm or less characterized by reduced tearing. A possible preferred separator membrane of the present invention uses one or more high molecular weight, low melt flow index polymer resins or blends that, when extruded using a dry process without the use of solvents and an extraction step, result in a higher crystalline thin film content in the precursor membrane (compared to previously known precursor membranes). When the precursor membrane with a higher crystalline thin film content is stretched to create pores, the resulting microporous membrane exhibits reduced tearing behavior, increased strength, higher porosity, lower electrical resistance, and lower gilli. The dry process microporous battery separators or membranes of the present invention, manufactured using high molecular weight, low melt flow index (MFI) polymeric resins, are equal to or surpass the performance characteristics of known wet process separators, can reduce or equalize the difference between dry process battery separator microporous membranes and wet process battery separator microporous membranes, and can reinforce or improve the battery cycle life and safety performance of lithium-ion secondary batteries.

[0074] The amount of crystallinity of the thin film layer structure of the precursor film can influence the formation of the porous microstructure of the dry process stretched microporous film. It is noted that the structure of the crystalline phase strongly influences the mechanical properties of the films in XM Zhang et al., “Oriented Structure and Anisotropy Properties of Polymer Blown Films HDPE, LLDPE and LDPE”, POLYMER 45 (2004) 217-229, and in S. Tabatabaei et al., “Microporous Membranes Obtained from PP / HDPE Multilayer Films by Stretching”, JMS 345 (2009) 148-159. Tearing resistance can be an important mechanical property for microporous films used in lithium-ion batteries. Microporous membranes may require sufficient mechanical strength to resist tearing during the harsh winding and / or fabrication stages of the battery, and these membranes may need to withstand the expansion and contraction forces that occur during repeated charge and discharge cycles throughout the battery's life.

[0075] The tear resistance of microporous membranes is often described using the term "tear" when tearing can be measured in MD or TD. A standard test method for measuring the mechanical strength of membranes is known as the puncture strength test. Fig. 1 is a photograph of a membrane sample undergoing a puncture strength test, in which the membrane sample is firmly clamped in place and a test needle is positioned to penetrate the sample. The puncture strength test measures the "load at break," where the compressive elongation in mm is expressed as a function of the load (gram-force).

[0076] Perforation strength test data enables the comparison of the mechanical strength performance of various porous membranes. Furthermore, this test method can be used to measure the resistance of a membrane to tearing or ripping when force is applied. When a membrane test sample is subjected to a perforation strength test, a test needle punctures the sample and leaves a mark or hole at the penetration site. In the research leading to the membrane of the present invention, it was determined that the shape of the perforation hole provides a tool that can be used to evaluate the membrane's resistance to tearing. It was found that membrane samples exhibiting excellent resistance to tearing have perforation holes that are round in shape, as shown in FIG. 2a, whereas membranes prone to tearing will tend to form elongated tear holes, such as the holes shown in FIG. 2b and FIG. 2c.

[0077] Battery separator membranes that tear during puncture strength testing may have a tendency to tear or break during the harsh battery winding stage in the fabrication of lithium-ion secondary batteries and / or during the use of such batteries. The force required to tear the membrane can be substantial. Easily torn battery separator membranes can lead to battery failure, which may occur due to direct or indirect contact between the battery electrodes and / or electrode particles penetrating the separator, causing an internal short circuit. Additionally, battery separator membranes observed to tear during puncture strength testing may potentially fail mechanically in the battery, allowing the positive and negative electrodes to come into contact, thereby causing an internal short circuit in the battery.

[0078] Tearing behavior was measured for a series of membranes used as battery separators for lithium-ion batteries. The measurement results are used to determine the mode of tearing or potential "tearing failure" of separators, such as microporous membrane separators or base films of specific batteries, by applying the test method of the present invention known as the Composite Tearing Index (CSI). Effects of the invention

[0079] The specific battery separators of the present invention described herein may have a thickness of about 14 μm or less and may exhibit increased strength performance, defined by a reduced tendency to tear or splittness when compared to known battery separators. Tearing failure modes have been studied, and improvements in tearing or splittness may be quantified by the novel test method disclosed herein as a composite tear index (CSI). The novel or improved membranes, films, or separators described herein may also exhibit improved glyphs as well as other improvements. Brief explanation of the drawing

[0080] Figure 1 is a photograph of a microporous membrane undergoing a puncture strength test. FIGS. 2a, 2b, and 2c include three close-up optical photographs of holes of different shapes resulting from puncture tests on three different microporous membrane or separator test samples, wherein FIG. 2a depicts the membrane or separator of the present invention and substantially round holes, and FIGS. 2b and 2c depict holes as elongated tears in comparison samples. Figures 3a and 3b include scanning electron micrographs (SEMs) of the surface of an etched nonporous polypropylene film showing a uniform and ordered structure of crystalline regions at two magnifications. Figure 4 is a stress-strain graph illustrating the behavior of PP and HDPE during stretching. Figure 5 is an SEM of the surface of a conventional microporous film, CE6, at a magnification of 20,000x. Figure 6 is an SEM of the surface of a conventional microporous film, CE5, at a magnification of 20,000x. FIG. 7 is a graph of the shear viscosity of selected resins and films according to various examples and comparative examples described herein. Figure 8 is a graph of the single-peak puncture strength test. Figure 9 is a graph of the double-peak puncture strength test. FIG. 10 is an SEM of the surface of Example 5 of the membrane or separator of the present invention, which is an exemplary invention. Figure 11 is an SEM of the surface of Comparison Example 1 of a conventional technology film. FIG. 12 is a photograph of Example 5 of the present invention illustrating a perforated hole having a substantially round shape. FIG. 13 is a photograph of Example 1 of the present invention illustrating a perforated hole having a substantially round shape. FIG. 14 is a photograph of Example 2 of the present invention illustrating a perforated hole having a substantially round shape. FIG. 15 is a photograph of Example 3 of the present invention illustrating a perforated hole having a substantially round shape. FIG. 16 is a photograph of a conventional film, CE4, showing a perforated hole having an elongated and / or slit-shaped hole. FIG. 17 is a photograph of a conventional film, CE2, showing a perforated hole having an elongated and / or slit-shaped hole. FIG. 18 is a photograph of a conventional film, CE1, showing a perforated hole having an elongated and / or slit-shaped hole. FIG. 19 illustrates a composite tear index (CSI) graph of the membranes of the present invention and the prior art. Specific details for implementing the invention

[0081] According to at least specific embodiments, aspects, or purposes, a novel or improved microporous battery separator has been developed for use in lithium batteries, such as lithium-ion rechargeable batteries. The separator membrane of the present invention is a dry-process monolayer or multilayer microporous battery separator or membrane preferably fabricated using a high molecular weight and low melt flow index polymer resin or a blend of high molecular weight and low melt flow index polymer resins, which, when extruded (without the need for plasticizers that must subsequently be extracted), generates a precursor membrane having an internal microstructure with a high level of crystalline thin film layer orientation. This high level of crystalline thin film layer orientation can lead to superior strength performance of the separator or membrane of the present invention. Manufacturers of batteries for the consumer electronics industry may prefer a thin microporous battery separator or membrane having a thickness of about 14 μm or less to optimize the energy density and lifespan of various lithium-ion secondary batteries, particularly energy batteries or cells. The battery separator or membrane of the present invention is a “thin” membrane battery separator, base film, or membrane having a thickness of preferably less than about 14 μm and having improved toughness and excellent strength performance, such as reduced tearing or ripping as a result of perforation, compared to other separators of the same thickness, for example, made by a conventional dry stretch process. Such microporous membranes and / or battery separators may be particularly useful in various fields where high-energy batteries are used.

[0082] The amount of crystalline thin film layer structure of the precursor film can play a role in the formation of micropores. Figures 3a and 3b show surface SEM of the stacked thin film layer structure of an etched nonporous polypropylene film that has not undergone MD or TD stretching. The etching process was performed to remove any amorphous portions, which enables better visualization of the crystalline thin film layer structure. Commonly known modes of pore formation in films are known in the industry and have been published in XM Zhang et al., “Oriented Structure and Anisotropy Properties of Polymer Blown Films HDPE, LLDPE and LDPE”, POLYMER 45 (2004) 217-229, and S. Tabatabaei et al., “Microporous Membranes Obtained from PP / HDPE Multilayer Films by Stretching”, JMS 345 (2009) 148-159. FIG. 4 is a conventional stress / strain graph illustrating the response of a nonporous membrane to applied stress, depicting the separation of stacked crystalline thin film plates by the initial application of stress. After this initial separation of the thin film plates, it is followed by further separating polymer chains from the thin film to form fibrils. Further extension of polymer fibrils to form the walls of the holes is shown in FIG. 4.

[0083] Figures 5 and 6 are SEM images illustrating the microscale appearance of the surfaces of conventional polypropylene (PP) microporous films (CE6 and CE5), where the crystalline thin film layer and microfiber structure are visible. A comparison of the crystalline thin film regions of CE6 and CE5 indicates that CE6 has thicker crystalline thin film regions. Furthermore, the pore size of CE6 is approximately twice the size of the pores of CE5. The CE6 and CE5 films are manufactured using polypropylene resins of different molecular weights having different melt flow indices that can play a role in the amount of the crystalline thin film layer formed during the melt extrusion of the precursor film (see Table 1).

[0084] membrane MFI (Melting Flow Index) of resins Crystallinity (%) Hole size (㎛) CE6 5.0 54.5% 0.064 CE5 1.5 47.5% 0.04

[0085] The amount of crystallinity of the thin film layer structure of the precursor film can be a factor in the formation of the internal porous microstructure of the dry-process stretched microporous film. It is noted that the structure of the crystalline phase can affect the mechanical properties of the film. (XM Zhang, et al. “Oriented Structure and Anisotropy Properties of Polymer Blown Films HDPE, LLDPE and LDPE”, POLYMER 45 (2004) 217-229.) The separator membrane of the present invention of at least selected embodiments may be manufactured by a dry process or a dry stretch process (also known as the CELGARD® dry process), and the membrane of the present invention may be monolayer or multilayer. In the case of a multilayer membrane or separator, the process may include: extruding PP and / or polyethylene (PE) nonporous precursors, for example, combining the nonporous precursors together in a PP / PE / PP laminated configuration to form a combined nonporous PP / PE / PP precursor, and stretching these precursors to form a microporous multilayer membrane, wherein the pore formation is nonporous, semicrystalline, in the machine direction It results from stretching the extruded polymer precursor. Additional stretching (e.g., TD) may also occur. An important mechanical property for microporous membranes used in lithium-ion batteries is tear resistance. Microporous membranes must have sufficient tear resistance to prevent tearing or ripping during battery winding and must be able to withstand the expansion and contraction forces that occur during repeated charge and discharge cycles throughout the battery's life.

[0086] The tear resistance of microporous membranes is often described using the term "tear" when tearing can be measured in MD or TD. A standard test method for measuring the mechanical strength of membranes is known as the puncture strength test. Figure 1 shows a photograph of a membrane sample clamped in place with a puncture strength test equipment setup in which a test needle is positioned to penetrate the test sample. The puncture strength test measures the compressive elongation (displacement) in millimeters due to the application of a load (stress). Figure 8 shows an example of a puncture strength graph, where the "load at failure" is determined as the maximum load at the point where the sample is punctured. Although 15 locations of the test sample were punctured in this example graph, typically 30 locations are tested, and the maximum load at failure is defined as the average. During this example, the applied load was increased to approximately 350 gram-force as the test membrane sample was displaced approximately 6 mm downward to the point where the sample was punctured. The observed linear relationship between the applied load and the resulting displacement of the test membrane produced a "single" peak graph.

[0087] Perforation strength test data enables the comparison of strength performance of various porous membranes. FIG. 9 is an example of a multilayer membrane separator or membrane of the present invention, wherein the test needle first perforates one layer of the membrane and proceeds to completely penetrate the test sample by the continuous application of a downward load, generating a two-peak graph. The first perforation is defined as the "first load peak," while the second perforation is defined as the "second load peak."

[0088] In addition to measuring the load required for rupture, this test method can be used to evaluate the resistance of the membrane against tearing or ripping caused by the application of force. During the puncture strength test, a needle punctures the test sample and leaves a puncture mark or hole at the penetration site. The shape of the puncture hole, as well as the load required to create the hole being measured, provides a tool that can be used to measure the comparative resistance of the membrane to tearing or ripping. The length of the hole (or the diameter if the puncture hole is round) was measured using a ruler to the nearest millimeter for commercial microporous membranes and various membranes according to the present invention. It was found that membrane samples exhibiting excellent resistance to tearing had a round hole shape as shown in FIG. 2a. In contrast, FIG. 2b shows a membrane that tore linearly to a length of 3.5 cm in one test and 9 mm in repeated tests as a result of the puncture strength test. Membranes that tear and mechanically fail in this manner are more prone to tearing during the harsh battery winding stage in battery manufacturing and are likely to fail to prevent the positive and negative electrodes from coming into contact during battery use, which leads to internal short circuits in at least certain batteries or fields.

[0089] The mechanical strength of porous membranes is also commonly evaluated by measuring tensile strength in the machine direction (MD) and the transverse direction (TD). The machine direction is defined as the longitudinal direction during sheet manufacturing, while the transverse direction is defined as the width direction during sheet manufacturing. Furthermore, the distance the membrane is stretched from its original size to the point of failure, defined as % elongation, can be important for evaluating the amount of twisting the membrane will undergo without failure. Percentage elongation can be measured in MD and TD.

[0090] Mechanical strength test data have been used to study modes of tearing or "tear failure" tendencies. A test method of the present invention known as the Compound Tear Index (CSI) has been developed, wherein the CSI value is defined by Equation 1 (described below), and the CSI is a function of the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during the puncture strength test.

[0091] CSI = (A-|B - A| 1.8 ) x C x (D x E) / 10 6 Equation 1

[0092] Here:

[0093] A = 1st load peak / thickness x (1 - % porosity)

[0094] B = Second load peak / Thickness

[0095] C = TD elongation

[0096] D = MD tensile strength

[0097] E = TD tensile strength

[0098] Here, the first and second load peaks are in gram-force units, the thickness values ​​are in microns, the MD and TD tensile strengths are in gram-forces, and the TD elongation is expressed as a percentage.

[0099] A high CSI value predicts a microporous film capable of having excellent strength performance in lithium-ion batteries, both during the expansion and contraction of the film that may occur during the battery cell winding stage of the fabrication process and during repeated charge and discharge cycles throughout the battery's lifespan.

[0100] Examples

[0101] Various microporous membranes or separators were made according to the present invention. In particular, Examples 1 to 5 were made as single-layer PP membranes or three-layer (PP / PE / PP) membranes and were made using various low MFI (melt flow index) polypropylene resins. Some of the examples included blends of polypropylene resins having slightly different (low) MFI values ​​(as shown in Table 2).

[0102] Table 2 below lists the resin and film characteristics of Examples 1 to 5 of the films of the present invention. In addition, comparative examples (CE1 to CE6) are provided to enable a comparison between the films of the present invention and conventional films.

[0103]

[0104] A = 1st load peak / thickness x (1 - % porosity)

[0105] B = Second load peak / Thickness

[0106] C = TD elongation

[0107] D = MD tensile strength

[0108] E = TD tensile strength

[0109] Ex.1 to Ex.3 are single-layer PP microporous membranes, whereas Ex.4 and Ex.5 are examples of three-layer PP / PE / PP microporous membranes. The membranes of the present invention have a thickness of about 13.5 μm or less, whereas the comparative membranes have higher thickness values ​​in the range of about 16 μm to about 25 μm, and CE4 to CE6 are more than three times thicker than Examples 1 to 3. The battery separator examples of the present invention (Ex.1, Ex.2, and Ex.3) are more than 46% thinner than the comparative prior art examples at comparative levels of % porosity and exhibit a significant increase in mechanical strength as defined by the CSI number. The CSI number is calculated using Equation 1 and is a function of thickness, % porosity, puncture strength, TD elongation, and MD and TD tensile strength.

[0110] The monolayer membranes of the present invention (Ex. 1 to Ex. 3), each having a thickness of approximately 7 μm, are extremely thin battery separators or membranes. For example, the PP monolayer membrane of the present invention (Ex. 2) has a CSI value of 138 at a thickness of 7 μm. A comparative PP monolayer example (CE1) having a thickness of 16 μm (more than twice the thickness of Ex. 1 to Ex. 3) has an even lower CSI value of only 16. Additionally, the three-layer membrane of the present invention (Ex. 5) has a CSI value of 141 at a thickness of 13.5 μm. The outer PP layers of the three-layer Ex. 5 were manufactured using a PP resin having an MFI value of 0.3 g / 10 min, demonstrating the benefits that a PP resin with a low MFI and higher molecular weight can contribute to the CSI value of the porous separator membrane. A comparative prior art 3-layer (CE2) with a thickness of 16.7 μm has a lower CSI value of -100, which predicts that such separators may have poor strength performance compared to the separators of the present invention during the expansion and contraction of the membrane that may occur during repeated charge and discharge cycles over the battery life for specific batteries, and during the battery cell winding stage of the fabrication process. A membrane with a low CSI value may tear and mechanically fail to prevent the positive and negative electrodes from coming into contact, which leads to an internal short circuit in the battery for specific batteries.

[0111] The films of the present invention may have a higher level of crystalline thin film layer because they are manufactured using one or more low melt flow index (MFI), higher shear viscosity, and high molecular weight polypropylene polymer resins. FIG. 7 illustrates the shear viscosity of the examples of the present invention compared to comparative examples. The films of Examples 1 through 5 have higher shear viscosity curves compared to CE 1, 3, 4, 5, and 6. The higher shear viscosity values ​​are a direct result of the lower MFI and higher molecular weight PP used to manufacture the examples of the present invention.

[0112] A comparison of the SEMs of the CE6 membrane shown in Fig. 5 and the membrane of the present invention (Ex. 5) shown in Fig. 10 reveals more general and uniform thickness regions of the crystalline thin film layers of the membrane of the present invention (Ex. 5) compared to CE6, as well as higher uniformity of these crystalline thin film layer regions. The smaller pore size of the membrane of the present invention should also be noted. Fig. 11 is an SEM of the surface of another comparative example (CE1), showing lower amounts of crystalline thin film layers and larger pores compared to the membrane of the present invention in Fig. 10. The high level of crystalline thin film layer orientation of the membranes of the present invention can play a role in the improved strength performance of the porous membrane and / or separator of the present invention. Furthermore, the uniformity of the highly crystalline thin film layer structure of the non-porous precursor membrane can play a role in the improved strength performance of the porous membrane and / or separator of the present invention. Furthermore, both the high level of crystalline thin film orientation of the non-porous precursor and the uniformity of the highly crystalline thin film structure can play a role in the formation of micropores during the stretching step. When a higher, more uniform crystalline thin film precursor is stretched to create pores, the resulting microporous film exhibits reduced tearing behavior and higher CSI values.

[0113] In the study of tearing modes, the puncture strength test illustrates that the membranes of the present invention have puncture holes of different shapes compared to comparative membranes. The membranes of the present invention have round puncture holes, whereas comparative prior art membranes may have a tendency to tear and may have elongated and / or slit-shaped holes. The shape of the holes at the puncture site during the puncture strength test provides an understanding of the tearing failure mode. FIG. 12 illustrates the round shape of the holes at the puncture site of Ex. 5 after the puncture strength test. The membranes of the present invention (Ex. 1, Ex. 2, and Ex. 3) illustrated in FIG. 13, 14, and 15 also have round holes at the puncture site after the puncture strength test. In contrast, the comparative examples (CE4, CE2, and CE1) illustrated in FIGS. 16, 17, and 18, respectively, have elongated and / or slit-shaped holes, representing mechanically weaker membranes that are more likely to tear during the harsh winding of the battery fabrication stage and / or during use for certain batteries. Furthermore, membranes exhibiting this tendency to tear during puncture strength testing will not be able to withstand the expansion and contraction forces that occur during repeated charge and discharge cycles throughout the life of the lithium-ion batteries for certain batteries. Tearing or tearing resistance can be an important requirement for the mechanical performance of microporous membranes for rechargeable lithium-ion batteries, particularly high-energy batteries or cells.

[0114] FIG. 19 is a graph of the composite tear index (CSI) calculated using Equation 1, plotted against the slit length of the hole in millimeters measured from the puncture strength test samples. The membranes of the present invention (Ex.1, EX.2, Ex.3, Ex.4, and Ex.5) have higher CSI values ​​and smaller puncture hole sizes (tear) than the comparative example (CE2), which indicates the superior mechanical strength performance of the membranes of the present invention and demonstrates that the selection of PP resins with higher molecular weight and lower melt flow index provides a novel path for tuning the mechanical properties of microporous membranes for lithium-ion batteries.

[0115] Test methods

[0116] thickness

[0117] Thickness is measured using an Embeco Microgage 210-A precision micrometer thickness tester according to the test process ASTM D374. Thickness values ​​are reported in units of micrometers, μm.

[0118] puncture strength

[0119] Test samples are pre-conditioned to 73.4°C and 50% relative humidity for a minimum of 20 minutes. An Instron Model 4442 is used to measure the puncture strength of the test samples. Thirty measurements are taken diagonally across a continuous 1 ¼” x 40” sample surface and averaged. The needle has a radius of 0.5 mm. The drop rate is 25 mm / min. The film is held tightly in a clamping device utilizing an O-ring to firmly hold the test sample in place. The diameter of this clamping area is 25 mm. The displacement (mm) of the film punctured by the needle is recorded against the resistance force (gram-force) generated by the tested film. The maximum resistance force is the puncture strength in units of gram-force (gf). A load-versus-displacement graph is generated by this test method.

[0120] Torn

[0121] The tear of the test sample is measured using a ruler (marked with increments from the nearest mm) to measure the length of the hole (or slit) that occurs as a result of penetration or puncture of the test sample by a needle during the puncture strength test. The tear is expressed in millimeters (mm) and is recorded as "hole size" in Table 2 above.

[0122] hole size

[0123] Pore ​​size is measured using Aquapore, available through Porous Materials, Inc. (PMI). Pore size is expressed in μm.

[0124] porosity

[0125] The porosity of a microporous film sample is measured using ASTM method D-2873 and is defined as a percentage of the void spaces of the microporous film.

[0126] TD and MD tensile strength

[0127] Tensile strength according to MD and TD is measured using an Instron Model 4201 according to the ASTM D-882 method.

[0128] Melt Flow Index (MFI)

[0129] The melt flow index of polymer resins is measured using ASTM DS 1238, and 2.16 kg of weight is used to measure the MFI of polyethylene at a temperature of 190°C; and 2.16 kg of weight is used to measure the MFI of polypropylene at a temperature of 230°C. The MFI is measured as grams per 10 min.

[0130] Electrical resistance (ER) (also known as ionic resistance (IR))

[0131] Electrical resistance is defined as the resistance value in ohms-cm² of a separator filled with electrolyte. The units of electrical resistance are ohms-cm². Separator resistance is characterized by cutting small pieces of separators from the finished material and then placing them between two blocking electrodes. The separators are saturated with a battery electrolyte containing 1.0 M LiPF6 salt of EC / EMC solvent in a 3:7 volume ratio. The resistance (R) of the separator, in ohms (Ω), is measured by the 4-probe impedance technique. To reduce measurement errors at the electrode / separator interface, multiple measurements are required by adding more layers. Based on multilayer measurements, the electrical (ionic) resistance (R) of the separator saturated with electrolyte is s (Ω)) then formula R s = p s Calculated by l / A, where p s ε is the ionic resistance of the separator in Ω-cm, A is the electrode area in cm², and l is the thickness of the separator in cm. R p s / A is slope = p s / A = ΔR / Δδ is the slope calculated for the change in separator resistance (ΔR) due to the multilayers (Δδ).

[0132] Get

[0133] The permeability is defined by the Japanese Industrial Standard (JIS) and measured using an OHKEN permeability tester. JIS permeability is defined as the time in seconds required for 100 cc of air to pass through 1 square inch of film at a static pressure of 4.9 inches of water.

[0134] According to at least selected embodiments, aspects, or purposes, one or more novel or improved porous membranes, base films, or battery separators and / or various methods for manufacturing and / or using such membranes, films, or separators are provided. According to at least specific embodiments, aspects, or purposes, the present invention relates to one or more novel or improved microporous membrane battery separators for lithium batteries, such as lithium-ion rechargeable batteries, and various methods for manufacturing or using such separators. The battery separators described herein may have a thickness of about 14 μm or less and may exhibit increased strength performance, defined by reduced tearing, when compared to known battery separators. Tear failure modes have been studied, and the improvement in tearing may be quantified by the test method disclosed herein as the Composite Tear Index (CSI). The novel or improved separators described herein may also exhibit improved Gurley as well as other improvements.

[0135] The present invention relates to a novel or improved microporous battery separator for a lithium-ion rechargeable battery in at least selected embodiments and / or related methods for manufacturing and / or using such separator. A particular dry-process battery separator or membrane separator of the present invention has a thickness of about 14 μm or less and has increased strength performance defined by reduced tearing. Tear failure modes have been studied, and the improvement in tearing is quantified by a novel test method known as the Composite Tear Index (CSI).

[0136] Preferred embodiments include the robust Celgard® brand battery separators of the present invention, designed to meet the requirements of battery and cell manufacturers and to provide excellent energy and / or power performance, dimensional integration, and chemical and thermal stability in the lithium battery field.

[0137] The present invention may relate to one or more novel or improved porous membranes, base films, or battery separators and / or various methods for manufacturing and / or using such membranes, films, or separators. According to at least selected embodiments, aspects, or purposes, the present application or invention relates to one or more novel or improved microporous membrane battery separators, membrane base films, or membrane separators for lithium batteries such as secondary or rechargeable lithium batteries, lithium-ion rechargeable batteries, etc., and / or various methods for manufacturing or using such separators and / or batteries. The specific battery separators of the present invention described herein may have a thickness of about 14 μm or less and may exhibit increased strength performance, defined by reduced tearing or rip when compared to known battery separators. Tear failure modes have been studied, and improvements in tearing or riping may be quantified by the novel test method disclosed herein as a Composite Tear Index (CSI). The novel or improved membranes, films, or separators described herein may also represent improved Gurley as well as other improvements.

[0138] The present invention relates to novel or improved microporous battery separators for lithium-ion rechargeable batteries in at least selected embodiments and / or related methods for manufacturing and / or using such separators. A particular dry-process battery separator or membrane separator of the present invention has a thickness of about 14 μm or less and has increased strength performance defined by reduced tearing. Tear failure modes have been studied, and the improvement in tearing is quantified by a novel test method known as the Composite Tear Index (CSI).

[0139] At least selected embodiments relate to improved base films or battery separators and / or methods for manufacturing and / or using such films, films or separators, dry process microporous battery separators or membrane separators, having a thickness of about 14 μm or less, a relatively low Gurley number, a relatively high porosity, and strength performance characteristics that are close to or exceed those of wet process battery separators or membrane separators, without the possible undesirable problems associated with various wet process fabrication methods for at least certain battery technologies or fields, energy fields and / or etc.

[0140] The present invention may be embodied in other forms without departing from its spirit and essential attributes, and thus, when defining the scope of the invention, the appended claims should be referenced rather than the foregoing specification. Additionally, the invention disclosed herein may be practiced without any elements not specifically disclosed herein.

Claims

Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 A single-layer separator for a lithium battery comprising a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the single dry process layer has a maximum melt flow index (MFI) of 0.8 g / 10 min, a thickness of 7 μm or less, a first load peak of 131 gf or more, a second load peak of 120 gf or more, a TD tensile strength in the range of at least 153-207 gf, an MD tensile strength of 1813 gf or more, and a TD elongation of 464% or more measured during a puncture strength test, wherein the strength performance prediction of the lithium secondary battery microporous membrane is performed through the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation rate measured during a puncture strength test. Claim 15 A separator for a lithium battery comprising a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the single dry process layer has a maximum melt flow index (MFI) of 0.8 grams / 10 min and a thickness of 7 μm or less, and the separator has a first load peak of 131 gf or more, a second load peak of 120 gf or more, and a TD tensile strength in the range of 153-207 kgf / cm2 with a maximum TD tensile strength of 207 kgf / cm2, and has a Composite Splittiness Index (CSI) for predicting the strength performance of a lithium secondary battery microporous membrane from the first load peak, second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 131 gf or more, the second load peak is 120 gf or more, and the TD tensile strength is A lithium battery separator having a tensile strength of 153-207gf or more, an MD tensile strength of 1813gf or more, and a TD elongation of 464% or more, wherein the separator is a single layer film or a base film. Claim 16 A separator for a lithium battery comprising a single dry process layer of homopolymer polypropylene or a polypropylene blend, wherein the single dry process layer has a maximum melt flow index (MFI) of 0.8 g / 10 min and a thickness of 7 μm or less, and the separator has a maximum TD tensile strength of 207 kgf / cm2 with a TD tensile strength in the range of 153-207 kgf / cm2, and has a Composite Splittiness Index (CSI) that predicts the strength performance of a lithium secondary battery microporous membrane from a first load peak, a second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 131 gf or more, the second load peak is 120 gf or more, the TD tensile strength is 153-207 gf or more, the MD tensile strength is 1813 gf or more, and the TD elongation is 464% or more, and the separator is a lithium battery separator that is a multilayer separator, a membrane, or a base film. Claim 17 A separator for a lithium battery, wherein the separator is a triple film or base film, and has a dry process triple film of a polypropylene blend having a maximum melt flow index (MFI) of 0.8 g / 10 min or less and a thickness of 14 μm or less, wherein the dry process triple film has a Composite Splittiness Index (CSI) of 70 or more, which predicts the strength performance of a lithium secondary battery microporous film from a first load peak, a second load peak, TD tensile strength, MD tensile strength, and TD elongation measured during a puncture strength test, wherein the measured first load peak is 279 gf or more, the second load peak is 277 gf or more, the TD tensile strength is 136-150 gf or more, the MD tensile strength is 2245 gf or more, and the TD elongation is 700% or more. Claim 18 In any one of claims 15 to 17, the separator in which the CSI value is defined by the following Equation 1. [Equation 1] CSI = (A - |B - A|1.8) x C x (D x E) / 106 (wherein: A = first load peak / thickness of the computer program, thickness = thickness x (100% - porosity), gfB = second load peak / thickness, gfC = TD elongation, %D = MD tensile strength, gfE = TD tensile strength, the unit of the gf thickness values ​​is μm) Claim 19 delete Claim 20 delete Claim 21 In claim 16 or 17, the separator is a separator having a porosity of 25% or more. Claim 22 In paragraph 16 or 17, the separator is 1.5 ohm-cm 2 A separator having an electrical resistance (ER) of the following and a porosity of 25% or more. Claim 23 In claim 16 or 17, the separator is a separator having 100 or more CSIs. Claim 24 In Clause 16, the separator is a separator having a CSI of 50 or more. Claim 25 In claim 16 or 17, the separator is a separator having a porosity of 27% or more. Claim 26 In claim 16 or 17, the separator is a separator having a porosity of 31% or more. Claim 27 In claim 16 or 17, the separator is a separator having a porosity in the range of 30% to 50%. Claim 28 In claim 16 or 17, the separator is a separator having a porosity in the range of 31% to 40%.

Citation Information

Patent Citations

  • Microporous membranes and methods for producing and using such membranes

    KR1020120116977A